2016
DOI: 10.2527/jas.2016-0409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of maternal vitamin D supplementation: I. Sow performance, serum vitamin metabolites, and neonatal muscle characteristics1,2

Abstract: IntroductIonThe most common form of dietary vitamin D supplemented in livestock diets is cholecalciferol (vi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 27 publications
8
45
3
Order By: Relevance
“…The data herein suggest that 2,000 IU of vitamin D/kg of diet were useful in achieving the highest growth rates compared to feeding 800 or 9,600 IU of vitamin D 3 /kg. Also, pigs weaned from sows fed 2,000 IU of vitamin D 3 /kg had numerically heavier weaning BW (although not statistically significant in the sow portion of the study; Flohr et al, 2016) than pigs from sows fed 800 or 9,600 IU of vitamin D 3 /kg. Pluske and Dong (1998) showed that the growth of suckling pig is predominately limited by the amount of milk produced by the sow.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The data herein suggest that 2,000 IU of vitamin D/kg of diet were useful in achieving the highest growth rates compared to feeding 800 or 9,600 IU of vitamin D 3 /kg. Also, pigs weaned from sows fed 2,000 IU of vitamin D 3 /kg had numerically heavier weaning BW (although not statistically significant in the sow portion of the study; Flohr et al, 2016) than pigs from sows fed 800 or 9,600 IU of vitamin D 3 /kg. Pluske and Dong (1998) showed that the growth of suckling pig is predominately limited by the amount of milk produced by the sow.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the amount of feed intake during lactation can impact total milk production and subsequent litter weaning weight (Eissen et al, 2003). Because of the increase in lactation ADFI observed for sows fed diets with 2,000 IU of vitamin D 3 /kg discussed by Flohr et al (2016), it is plausible to think that lactation feed intake may have been a larger reason for the numeric increase in weaning weights of pigs rather than maternal vitamin D treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations